Description of Toddler Mother's Knowledge of Stunting in Forestry Hamlet, Secanggang Village, Langkat District - Nurhayati, Nurhayati; Andin, Munanda; Purba, Dwi Syahputri; Panggabean, Diani Sari (Universitas Muhammadiyah Semarang, 2024)
Background: Lack of nutritional intake is a significant factor causing stunting in children, affecting their growth and development. The role of maternal knowledge and parenting practices is crucial in preventing stunting.Objective: In This study aims to determine the relationship between maternal knowledge and stunting in toddlers in Forestry Hamlet, Secanggang Village, Langkat Regency.Methods: A descriptive quantitative research design was employed. Data were collected using questionnaires from a sample of 30 mothers of toddlers. The study analyzed the knowledge levels of these mothers regarding stunting.Results: The analysis revealed that 70% of mothers had good knowledge, 26.7% had sufficient knowledge, and 3.3% had poor knowledge about stunting. The findings suggest that higher education levels among mothers are associated with better knowledge about preventing stunting.Conclusion: There is a significant relationship between maternal knowledge and the incidence of stunting in toddlers. Enhancing health education and promoting better understanding of toddler nutrition among mothers can contribute to reducing stunting rates. Health services and authorities should focus on disseminating information through various media to improve maternal knowledge and practices related to child nutrition.